Pelatihan Pembuatan Dodol Jagung Pada Masyarakat Desa Yudha Karya Bakti Kecamatan Sukakarya Kabupaten Musi Rawas - Nopa Nopiyanti; Reny Dwi Riastuti (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Yudha Karya Bakti Village has enormous potential, namely Natural Resources such as corn plants. Where this corn is usually only processed as ordinary corn food such as, boiled, corn grits to be eaten by the community. Corn dodol is a food product that is made into a special food for the people of Yudha Karya Bakti Village. All types of corn found in Yudha Karya Bakti Village can be used as ingredients for making this corn dodol. By exploiting the potential of natural resources that come from the agricultural gardens of the residents. So innovation efforts are made to take advantage of this potential to empower the community to create innovations or food products that have high selling values that reach all aspects of society. Because most of the community is a subsistence farmer, the training is expected to increase the income of the community during their free time while farming.